2017
DOI: 10.4162/nrp.2017.11.5.419
|View full text |Cite
|
Sign up to set email alerts
|

Circulating folate levels and colorectal adenoma: a case-control study and a meta-analysis

Abstract: BACKGROUND/OBJECTIVESThe relationship between folate and colorectal neoplasia remains controversial. We examined the association between serum folate concentrations and colorectal adenomas in a case-control study of Korean adults and conducted a meta-analysis.SUBJECTS/METHODSOur case-control study included 113 pairs of case and control who underwent colonoscopy and provided blood samples. We used multivariable conditional logistic regression models to obtain the odds ratios and 95% confidence interval (CIs). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…For example, although total fiber intake was not associated with overall conventional adenomas or SPs, it was associated with lower risk advanced conventional adenomas, in line with the meta-analysis findings that fiber was associated with a lower risk of CRC. 57 Similarly, we confirmed previous findings that intake of total calcium, vitamin D, and folate was inversely associated with risk of conventional adenomas 58-60 . In contrast, we did not find any association between calcium and folate intake and risk of SPs.…”
Section: Discussionsupporting
confidence: 90%
“…For example, although total fiber intake was not associated with overall conventional adenomas or SPs, it was associated with lower risk advanced conventional adenomas, in line with the meta-analysis findings that fiber was associated with a lower risk of CRC. 57 Similarly, we confirmed previous findings that intake of total calcium, vitamin D, and folate was inversely associated with risk of conventional adenomas 58-60 . In contrast, we did not find any association between calcium and folate intake and risk of SPs.…”
Section: Discussionsupporting
confidence: 90%
“…The current evidence indicates a clear link between folate metabolism and the development of both CRA and CRC. In a meta-analysis of eleven epidemiologic studies by Park et al, low folate levels were associated with a greater prevalence or incidence of colorectal adenomas, suggesting that low folate may contribute to colorectal cancer in the early stages [ 31 ]. Numerous studies have found that folate intake was inversely associated with colorectal cancer and adenoma risk, with the highest folate intake depicting a 20–40% lower risk [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Folate deficiency is reportedly associated with the development of neural tube defects and congenital disorders, anemia, atherosclerosis, adverse pregnancy outcomes, neuropsychiatric disorders, and cognitive impairments [3]. Accumulating epidemiological evidence suggests an inverse relationship between dietary folate intake or blood folate levels and the risk of multiple malignancies, including lung, oropharyngeal, esophageal, stomach, colorectal, prostate, and breast cancer [3][4][5][6][7]. However, clinical and preclinical studies suggest that excess FA consumption is associated with an increased risk of progression of established precancerous lesions, indicating that folate may play a dual modulatory role in cancer development and progression [5,6,[8][9][10].…”
Section: Introduction *mentioning
confidence: 99%